Reason, Culture, Religion - Pettman, R. author. aut Link
208 p.
Keywords: Reason, Culture, Religion book provides a systematic overview of the study of world politics. The author then locates modernist world politics in its sacral context by discussing Taoist strategics, Buddhist economics, Islamic civics, Confucian Marxism, Hindu constructivism, Pagan feminism and Animist environmentalism. It concludes by asking what a world affairs worthy of the name would be.